Isolated cores in early-type disk galaxies: NGC 4672 - Corsini, E; Sarzi, M; Pizzella, A; Cappellari, M; Bertola, F; Funes, J; Beltran, J (2000)
The morphological features of the early-type disk galaxy NGC 4672 are discussed as well as the velocity curves and velocity dispersion profiles of stars and ionized gas along both its major and minor axes. We conclude that NGC 4672 has structural (i.e. a bulge elongated perpendicularly to the disk) and kinematical (i.e, a stellar core rotating perpendicularly to the disk) properties similar to those of the Sa NGC 4698. The presence of the isolated core suggests that the disk component is the end result of the acquisition of external material in polar orbits around a pre-existing oblate spheroid, as in the case of the ring component of AM 2020-504, the prototype of polar ring ellipticals.